Continuous Glucose Monitoring and Physical Activity - Schubert-Olesen, Oliver; Kroeger, Jens; Siegmund, Thorsten; Thurm, Ulrike; Halle, Martin (International Journal of Environmental Research and Public Health, 2022)
Continuous glucose monitoring (CGM) use has several potential positive effects on diabetes management. These benefits are, e.g., increased time in range (TIR), optimized therapy, and developed documentation. Physical activity is a recommended intervention tool in diabetes management, especially for people with type 2 diabetes (T2D). The benefits of physical activity for people with diabetes can be seen as an improvement of glycemic control, glycemic variability, and the reduction of insulin resistance. In relation to the physical activity of people with T2D, the benefits of CGM use can even be increased, and CGM can be a helpful tool to prevent adverse events due to physical activity of people with diabetes, such as hypoglycemic events and nocturnal hypoglycemia after sports. This narrative review aims to provide solid recommendations for the use of CGM in everyday life physical activities based on the noted benefits and to give a general overview of the guidelines on physical activity and CGM use for people with diabetes.
CRIS-Team Scopus Importer:2023-03-08
Keywords: continuous glucose monitoring; diabetes mellitus; physical activity